Pelaksanaan pembangunan balok lantai 2 gedung Pondok Pesantren Ashhaburratib untuk mendukung kegiatan pembelajaran - Jonathan Saputra; Lilis Tiyani; Yuwono (Abdimas Siliwangi, 2025)
Ashhaburratib Islamic Boarding School is an institution that operates in the field of social education. However, the condition of the Islamic boarding school building is in poor condition due to problems on the 2nd floor of the Islamic boarding school building. The owner of the Islamic boarding school has started efforts to build the second floor to accommodate the increase in students, but has stopped at the stage of installing reinforcements for the columns in one of the buildings. The unsustainability of this development was due to the death of the Islamic boarding school owner, so that on the 2nd floor of the building only reinforcement and columns were installed. To deal with this problem, the Abdimas Team held a Community Service program entitled "Implementation of Beam Work on the 2nd Floor of the Ashhaburratib Beji Islamic Boarding School Building, Depok, West Java". This program is held in order to implement the Tri Dharma of Higher Education and is a routine and programmed matter to help solve problems faced by the community. Beams are an important part of a building structure and are the part of the structure that functions to support the load of the upper structure and distribute it to the columns.